National Museum of Western Art as Important Cultural Property of Japan: its Evolution and Historical Value - Yamana, Yoshiyuki; Fukuda, Kyo (Docomomo Journal, 2015)
Starting with the conception of the World Museum as part of the 1929 Mundaneum project, Le Corbusier continued to develop and refine that concept. The main building of the National Museum of Western Art completed in 1959, was also designed as a Museum of Unlimited Expansion prototype. NMWA has undergone conservation work and seismic base isolation work a number of times, and is therefore in generally good condition. The principal conservation works to the main building since its completion is summarized in this essay, along with other construction, extension and maintenance work carried out on the grounds.